Examining Fernando Sor’s Étude Books Written for Classical Guitar - İbrahim Şevket Güleç (Konservatoryum)
As virtuosity on the classical guitar gained importance in the early 19th century, a parallel increase occurred regarding methodological compositions. Guitarists and composers who conducted these works include Ferdinando Carulli (1770-1841), Fernando Sor (1778-1839), Francesco Molino (1768-1847), Matteo Carcassi (1792-1853), and Dionisio Aguado (1784-1849). Among these pioneering artists, Fernando Sor had a method and composed six étude books that are still used in modern classical guitar education. Technical analyses of the composer’s selected works have been addressed in the literature. Accordingly, the current study has identified its issue to be what the technical elements are in all of the composer’s étude books. The distribution of the étude books according to left- and right-hand techniques is shown in organized tables, with the purpose here being to visually present the technical distributions according to the études. This way, performers can easily identify the techniques on which they want to focus. When examining the tables, the most preferred technique in all the étude books is melody accompaniment, followed by chords, intervals, arpeggios, legato, barre, muting, ornaments, scales, agility, thumb, harmonics, tremolo, position jumping, and glissando. This situation emphasizes how important musical expression is in Sor’s étude books.